Challenging the linearity assumption of intra-brand image confusion - Malek Simon Grimm; Ralf Wagner (Journal of Marketing Analytics, 2022)
The purpose of this study is to clarify and consolidate the components and consequences of intra-brand image confusion (IBIC). In addition to validating previous research results on IBIC in a fresh context (different product category with its brands), this study challenges the linearity assumption usually underlying studies of branding impacts and IBIC. A national representative online survey was conducted in the United Kingdom investigating the smartphone market. Explorative factor analyses were conducted in order to assess the components of IBIC. Structural equation modeling reveals the extent and consequences of IBIC. Multiple regressions were conducted to further explore non-linear response at the sub-domain and higher-order construct level. The results confirm and solidify previous results on the relevance of the construct of IBIC. This study supports the relevance of intra-brand image confusion's three components. A novel contribution arises from the fact that customers with a moderate involvement level are more confused than people with lower involvement levels. A U-shaped response indicates that lower involved prospective customers are at higher risk of a confusion by too broad assortments. Brand managers are well advised to pay strong attention to the structure of an assortment and to sub-brands to prevent the occurrence of an IBIC.
Keywords: 650; Intra-brand image confusion; Brand portfolios; Assortment; Brand image; Portfolio strategy; Non-linear effect